Advokátní praxe v rodinném domě - Čapek, Aleš (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Ke své bakalářské práci jsem přistupoval v souladu s řešením moderního rodinného domu při snaze o jednoduchost tvaru i samotné konstrukce. Jedná se o dvoupodlažní rodinný dům s provozovnou nacházející se v nové zástavbě v Havlíčkově Brodě. Téměř čtvercové dolní podlaží, které je částečně zaříznuté do terénu, slouží pro podnikání a horní podlaží, které se esovitě rozšiřuje směrem do zahrady, je navrženo jako soukromá část objektu s vlastním vchodem. Hlavní dispoziční myšlenkou tedy bylo oddělení části soukromé od veřejné. Ze stavebního pohledu byla snaha využít vhodnou kombinaci materiálů pro potlačení jejich nevýhod a tedy pro celkové zpříjemnění užívání stavby.

To my undergraduate work, I approached in accordance with the solution of the modern detached house in pursuit of simplicity in both, form and structure itself. It is about a two-storey house with an practice area located in the new built-up district in Havlickuv Brod. Almost square bottom floor, which is partialy cut into the ground is used for business and the upper floor, which extends S-shaply towards the garden, is designed as a private part of the building with its own entrance. The main disposal idea thus was the separation of private area from public. From the construction point of view was an effort to use a suitable combination of materials for suppressing their disadvantages and thus for overall more comfortable usage of the building.
Detached House with Lawyer Practice
Keywords: rodinný dům s provozovnou; dvoupodlažní objekt ve svahu; plochá obrácená střecha; detached house with an practice area; two-storey building on a slope; flat turned-up roof